Economic Incentives, Perceptions and Compliance with Marine Turtle Egg Harvesting Regulation in Nicaragua - Madrigal-Ballestero, Róger (2017)
La Flor Wildlife Refuge and nearby beaches on the Pacific coast of Nicaragua are important nesting sites for various species of endangered marine turtles. However, illegal harvesting of turtle eggs threatens the survival of marine turtles. In this study, we analysed the different motivations of local villagers for complying with a ban on harvesting marine turtle eggs in a context, in which government authorities do not have the means to fully enforce existing regulations. We also analysed the effectiveness and the participation of locals in an incipient performancebased nest conservation payment programme to protect turtle eggs. The analysis of survey-based data from 180 households living in Ostional, the largest village near La Flor Wildlife Refuge, indicates remarkable socio-economic differences between harvesters and non-harvesters. Our findings suggest that harvesters are associated mainly with a lack of income from other activities and the absence of productive assets, such as land for cattle and/or agriculture. In addition, the lack of legitimacy of prevailing institutions (i.e., actual regulations) also seems to perpetuate illegal harvesting. The performance-based payments programme is an effective option for protecting nests on isolated beaches, however, it is not clear if it changes harvesting behaviour overall. Normative motivations to protect the turtles are important determinants of participation in this programme, although the financial reward is also an important incentive, particularly since most participants who are egg harvesters depend on this activity as their main source of income.